A systematic review of methods for identifying drought-flood abrupt alternation: advances and future directions - Zhao, Lin; Aiyub, Kadaruddin; Ata, Frankie Marcus; Lam, Kuok Choy; Sun, Mengzhu (Frontiers in Environmental Science, 2025)
Drought-flood abrupt alternation (DFAA) events, characterized by compound extremes and rapid transitions, pose significant challenges for accurate identification. Although existing research has reviewed DFAA event identification, it pays insufficient attention to emerging concepts related to DFAA and characterization variables and lacks a comprehensive summary of methodological advancements under climate change. To fill these gaps, this study systematically reviews 55 publications by proposing a unified definition framework, synthesizing identification and characterization methods, evaluating recent methodological advances, and outlining future directions for improving DFAA identification. This review shows that (1) 58% of studies utilize traditional drought-flood indices and indicators, whereas 42% propose DFAA-specific indices; (2) traditional methods often disregard key DFAA characteristics, treating droughts and floods as separate events rather than as a unified process; (3) advanced methods incorporate key features such as alternation points, transition time, and transition speed, yet challenges remain in accurately capturing abrupt transitions; (4) future research should integrate multi-source datasets and apply dynamic time windows to improve DFAA identification, while aligning advances with policy to strengthen early warning and risk management.